Understanding and Mitigating Interpersonal Communication Conflict in Field‐Based Institutions. Issue 1 (13th December 2022) - McDermott, Victoria; Kauten, Rebecca; Gee, Jennifer; May, Amy
Abstract: Interpersonal communication conflict is an inevitable part of field‐based experiences due to the many complex variables that influence human interactions, such as culture, gender, and perceived power. Moreover, in field‐based institutions (i.e., field stations and marine laboratories) privacy may be limited in terms of space and time, and physical conditions may be challenging, which can lead to more frequent and intense interpersonal conflicts. Conflicts can arise episodically or cyclically at a field‐based institution, impacting visitors and employees at all levels, that is, between students, staff, faculty, and leadership. Those who work seasonally or permanently at field‐based institutions may be able to mitigate some of the potential negative outcomes associated with unmanaged conflict by knowing when these incidents might occur, as well as how to employ meaningful conflict management strategies during these times. Thus, we propose the 10/60 model of field station experiences to define significant points of time during a field experience in which collecting feedback may be critical for avoiding communication conflict. We provide additional recommendations on best practices for soliciting feedback, as well as the importance of setting explicit communication expectations for those in leadership positions to create more inclusive and equitable spaces.